MATHEMATICS TEACHERS' BELIEFS ABOUT LEARNING AND TEACHING MATHEMATICS - Rafah Riyadh Khazzal (Scholars Digest Publishing, 2025)
The current study aimed to explore the beliefs of mathematics teachers regarding the learning and teaching of mathematics. To achieve the objective of the study, the Mathematics Teaching and Learning Beliefs Scale developed by Beswick (2005) was utilized after being translated and modified. The original scale consists of 26 items distributed across three domains: the nature of mathematics, learning mathematics, and teaching mathematics. However, since the focus of this study was limited to learning and teaching mathematics, only 24 items were used, excluding the two items related to the nature of mathematics. The results of the study indicated that the beliefs of mathematics teachers tend to align with the contemporary (constructivist) perspective of learning and teaching mathematics. Specifically, 11 out of the 20 items reflecting the modern view received high mean scores. The findings also showed that there were no statistically significant differences in teachers’ beliefs about learning and teaching mathematics attributable to gender. However, statistically significant differences were found based on the academic qualification variable. In light of these findings, the researcher recommends organizing workshops and training programs based on constructivist theory. These should emphasize learner-centered activities and the process of constructing mathematical knowledge through prior experiences, which in turn positively influences teachers’ beliefs about learning and teaching mathematics.
Keywords: Beliefs, Mathematics Teachers, Teachers’ Beliefs